Deep learning for predicting the risk of immune checkpoint inhibitor-related pneumonitis in lung cancer. Issue 5 (May 2023) - Cheng, M.; Lin, R.; Bai, N.; Zhang, Y.; Wang, H.; Guo, M.; Duan, X.; Zheng, J.; Qiu, Z.; Zhao, Y.
Abstract : AIM: To develop and validate a nomogram model that combines computed tomography (CT)-based radiological factors extracted from deep-learning and clinical factors for the early predictions of immune checkpoint inhibitor-related pneumonitis (ICI–P). MATERIALS AND METHODS: Forty ICI–P patients and 101 patients without ICI–P were divided randomly into the training ( n= 113) and test ( n= 28) sets. The convolution neural network (CNN) algorithm was used to extract the CT-based radiological features of predictable ICI–P and calculated the CT score of each patient. A nomogram model to predict the risk of ICI–P was developed by logistic regression. RESULTS: CT score was calculated from five radiological features extracted by the residual neural network-50-V2 with feature pyramid networks. Four predictors of ICI–P in the nomogram model included a clinical feature (pre-existing lung diseases), two serum markers (absolute lymphocyte count and lactate dehydrogenase), and a CT score. The area under curve of the nomogram model in the training (0.910 versus 0.871 versus 0.778) and test (0.900 versus 0.856 versus 0.869) sets was better than the radiological and clinical models. The nomogram model showed good consistency and better clinical practicability. CONCLUSION: The nomogram model that combined CT-based radiological factors and clinical factors can be used as a new non-invasive tool for the early prediction of ICI–P in lung cancer patients after immunotherapy with low cost and low manual input. Highlights: Immune checkpoint inhibitor-related pneumonitis in lung cancer after immunotherapy. Residual neural network-50-V2 with feature pyramid networks from deep learning. CT-based radiological features combined with convolution neural network. A nomogram model to predict immune checkpoint inhibitor-related pneumonitis.